THE CONCEPT OF LAND DISPUTES IN LAND LAW 2013 - Lê Thị Bích Chi (Tạp chí Khoa học Đại học Đà Lạt)
Land disputes are now very common with complicated factors, arising in many relevant legislation relationships such as inheritance, divorce, contracts, etc. The land law at present, however, has an inconsistent resolution process, due to controversial ideas of the concept of land dispute. In order to identify exact authorities and resolution procedures, it is significant to clarify the meaning and scope of this term. As a result, this will avoid crowded and persistent complaints or litigation with incoresponding steps, which has been harmful to society’s safety and common order. Based on researching the practical resolution of land disputes in recent years, current relating regulations, and scholars’ opinion on the concept of land disputes and disputes over a land use right, we will provide our points of view on these notions.